Mutation mapping and functional characterization of a missense mutation p.Arg228Cys in ALDH3A2 gene causing Sjögran-Larson syndrome - Muhammad Zeeshan Ali; Samia Sattar; Abdulfatah M. Alayoubi; Shakil Abbas; Mohammed Turki Hussain Alharthi; Alwaleed Fahad H. Altemani; Muhammad Latif; Muzammil Ahmad Khan; Christian Windpassinger (Molecular Biology Reports, 2026)

Classification of decomposed neural data in memory networks and LLM-based stimuli processing - Muhammad Shahzaib; Salma Zainab Farooq; Eric H. Schumacher; Shella D. Keilholz; Sadia Shakil (Brain Imaging and Behavior, 2026)

Identifying necessary and sufficient conditions for enhancing loyalty in hybrid electronic vehicles: A combined PLS-SEM and NCA approach - Sung-Yong Choi; Jae-Jang Yang; Muhammad Shakil Ahmad; Yong-Ki Lee (Travel Behaviour and Society, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Assessment of antiemetic potential of schaftoside through modulation of dopaminergic, serotonergic and muscarinic signaling pathways: in vivo and in silico investigations - Md. Shakil Ahmmed; Rakib Hossan; Tawfik Rakaiyat Ripu; Towfiqur Rahman; Mohammad Y. Alshahrani; Emon Mia; Proma Mandal; Md. Sakib Al Hasan; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correction: Quantification of Heavy Metal Contamination and Assessment of Associated Environmental Risks from E-Waste Recycling in Pakistan - Sidra Shakil; Sunia Zahid; Ayesha Baig; Muhammad Saqib; Manel Ben Ali; Bander Albogami; Amor Hedfi (Bulletin of Environmental Contamination and Toxicology, 2026)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

Antiemetic Efficacy of Nodakenin Through Muscarinic, Dopaminergic, and Serotonergic Receptor Modulation: Combined Experimental and Computational Approach - Towfiqur Rahman; Feroz Khan Nun; Tawfik Rakaiyat Ripu; Md. Sakib Al Hasan; Md. Shakil Ahmmed; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Imam Hossen Rakib; Emon Mia; Md. Shimul Bhuia; Muhammad Torequl Islam (Cell Biochemistry and Biophysics, 2025)

Polyethylene Glycol Mitigates Cadmium Toxicity in Raphanus sativus L. by Regulating Enzymatic and Nonenzymatic Antioxidant Defence Mechanisms - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Journal of Soil Science and Plant Nutrition, 2025)

Quantification of Heavy Metal Contamination and Assessment of Associated Environmental Risks from E-Waste Recycling in Pakistan - Sidra Shakil; Sunia Zahid; Ayesha Baig; Muhammad Saqib; Manel Ben Ali; Bander Albogami; Amor Hedfi (Bulletin of Environmental Contamination and Toxicology, 2025)

Genetic analysis in a consanguineous MCPH family revealed a refinement of the MCPH12 locus and a founder effect of the recurrent CDK6 variant [c.589G>A, p.(Ala197Thr)] in the Pakistani population - Muzammil Ahmad Khan; Jasmin Blatterer; Markus Kuster; Lukas Kaufmann; Peter M. Kroisel; John B. Vincent; Muhammad Zubair; Muhammad Muzammal; Nisar Ahmad; Shakil Abbas; Wasim Shah; Muhammad Zeeshan Ali; et al. (Journal of Genetics, 2025)

Spatiotemporal dynamics of water and sediment characteristics in Kaptai Lake: implications for sustainable management - Saifuddin Rana; Mohammad Shakil Khan; Farhan Azim; Muhammad Obaidullha; Ariful Islam Milon; Zobair Alam Sunny; Sk. Ahmad Al Nahid; Shahida Arfine Shimul (Environmental Monitoring and Assessment, 2025)

Synthesis and optimization of fluoxetine-loaded polymeric nanoparticles for dual therapeutic applications in cancer and depression - Muhammad Shoaib; Hira Arif; Asia Naz Awan; Moona Mehboob Khan; Sehrish Batool; Shakil Ahmed (DARU Journal of Pharmaceutical Sciences, 2025)

High-resolution monthly gridded temperature dataset development and trend analysis across Afghanistan: a spatio-temporal approach - Maghfoorullah Tasal; Shakil Ahmad; Muhammad Azmat; Mohammad Uzair Rahil; Khalil Ahmad (Theoretical and Applied Climatology, 2025)

Genome-wide association study and genomic prediction for pod-shattering tolerance in a diverse rapeseed/canola germplasm collection - Shakil Hosain; David P. Horvath; Jayanta Roy; Ahasanul Hoque; Muhammad Arifuzzaman; Mukhlesur Rahman (Euphytica, 2025)
Pod-shattering in rapeseed/canola results in significant yield loss. In this study, a diverse spring-type rapeseed/canola germplasm consisting of 146 accessions was evaluated for pod-shattering tolerance in five environments under field and greenhouse conditions. The genome-wide association study (GWAS) was conducted using 24K single nucleotide polymorphisms (SNPs) markers obtained through genotyping-by-sequencing (GBS). Eight GWAS approaches were employed which identified 21 SNPs for pod-shattering. The phenotypic variation explained by these SNPs ranged from 3.8 to 25.4%. The SNP positions located on chromosomes A01, A03, A05, A06, A09, C02, C03, C05, and C08 have been previously reported to be associated with shattering. Two strong candidate genes, INDEHISCENT ( IND ) and MANNANASE7 ( MAN7 ), located on chromosome A03 (20.5 Mbp position) and chromosome C04 (61.1 Mbp position), respectively, were identified for the pod shattering trait. Genomic prediction (GP) was conducted with 24K SNPs using 14 prediction models. The prediction ability of all models ranged from 0.18 to 0.50 across five different environments. To determine the minimum number of markers needed to estimate the predictive ability, we used 25 to 20,000 randomly selected markers where 3000 to 20,000 markers gave a similar prediction ability (≈0.47). This study provides significant insight and elevates our understanding of the genetic architecture of pod-shattering in canola and suggests that SNP markers and GP have the potential to select pod shattering resistant germplasm at an early stage for use in a breeding program.

Insight into polyethylene glycol-mediated physiochemical, nutritional, and antioxidative defense modulations in salt-stressed Raphanus sativus L - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Physiology and Molecular Biology of Plants, 2025)

Hydro-Climatic variability in the Potohar Plateau of Indus River Basin under CMIP6 climate projections - Ahsan Ullah Khan; Shakil Ahmad; Khalil Ahmad; Muhammad Azmat; Zakir Hussain Dahri; Muhammad Wasif Khan; Zafar Iqbal (Theoretical and Applied Climatology, 2025)

Synergistic performance of an in-house synthesized cationic Gemini surfactant for enhanced oil recovery under harsh conditions - Khaled Al-Azani; Sidqi Abu-Khamsin; Mohammed Alotaibi; Muhammad Shahzad Kamal; Syed Muhammad Shakil Hussain; Mohanad Fahmi; Shirish Patil (Fuel, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Developing high resolution monthly gridded precipitation dataset for Afghanistan - Mohammad Uzair Rahil; Shakil Ahmad; Muhammad Wasif Khan; Ammara Mubeen; Zakir Hussain Dahri; Khalil Ahmad; Muhammad Arshad; Rahmatullah Wahdatyar (Theoretical and Applied Climatology, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Binary mixture of ionic liquid and span 80 for oil spill remediation: Synthesis and performance evaluation - Masooma Nazar; Aqeel Ahmad; Syed Muhammad Shakil Hussain; Muhammad Moniruzzaman (Marine Pollution Bulletin, 2024)

Retraction Note: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md.Mominur Rahman; Md.Rezaul Islam; Sheikh Shohag; Md.Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md.Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md.Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2024)

Spatio-temporal patterns of human-carnivore conflict and mitigation in Pakistan - Muhammad Danish; Tariq Mahmood; Faraz Akrim; Muhammad Sajid Nadeem; Shumaila Noreen; Nadeem Munawar; Muhammad Shakil; Muhammad Arshad (Journal for Nature Conservation, 2023)

Development of high resolution daily gridded precipitation and temperature dataset for potohar plateau of indus basin - Muhammad Wasif Khan; Shakil Ahmad; Zakir Hussain Dahri; Zain Syed; Khalil Ahmad; Firdos Khan; Muhammad Azmat (Theoretical and Applied Climatology, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Development of methods for the simplification of complex group built causal loop diagrams: A case study of the Rechna doab - Muhammad Asif; Azhar Inam; Jan Adamowski; Muhammad Shoaib; Hisham Tariq; Shakil Ahmad; Mohammad Reza Alizadeh; Aftab Nazeer (Ecological Modelling, 2023)

The role of various ameliorants on geochemical arsenic distribution and CO2-carbon efflux under paddy soil conditions - Muhammad Mahroz Hussain; Irshad Bibi; Fawad Ali; Zulfiqar Ahmad Saqib; Muhammad Shahid; Nabeel Khan Niazi; Khalid Hussain; Sabry M. Shaheen; Hailong Wang; Qamar Shakil; Jörg Rinklebe (Environmental Geochemistry and Health, 2023)

Haemodialysis alters the serum metal contents in chronic kidney failure patients at hyderabad and adjoining areas - Marvi Shaikh; Naseem Aslam Channa; Ali Muhammad Wahryah; Muhammad Haneef Mugheri; Shakil Samejo; Lubna Noorani (BioMetals, 2023)

Bioaccumulation and Health Risk Assessment of Heavy Metal (loid)s in Different Fish Species of Hainan Island, China - Tauseef Ahmad; Sumaira Gul; Muhammad Amjad Khan; Xiaoping Diao; Ashfaq Ahmad; Shakil Ahmad (Thalassas: An International Journal of Marine Sciences, 2022)

Correction to: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Scholarly output of energy and fuels research in Saudi Arabia during 1972–2020: a bibliometric analysis - Mohammad Aqil; Muhammad Abdul Mujeebu; Shafiq Ur Rehman; Shakil Ahmad (Arabian Journal of Geosciences, 2022)

Efficacy of various natural plant extracts and the synthetic insecticide cypermethrin 25EC against Leucinodes orbonalis and their impact on natural enemies in brinjal crop - Mehran Ullah; Farman Ullah; Muhammad Anwar Khan; Shakil Ahmad; Momana Jamil; Sapna Sardar; Kaleem Tariq; Nazeer Ahmed (International Journal of Tropical Insect Science, 2022)

Spatio‐temporal evaluation of gridded precipitation products for the high‐altitude Indus basin - Zakir Hussain Dahri; Fulco Ludwig; Eddy Moors; Shakil Ahmad; Bashir Ahmad; Muhammad Shoaib; Irfan Ali; Muhammad Shahid Iqbal; Muhammad Saleem Pomee; Abdul Ghafoor Mangrio; Muhammad Munir Ahmad; Pavel Kabat (International Journal of Climatology, 2021)
The high‐altitude Indus basin is one of the most complex and inadequately explored mountain terrains in the World, where reliable observations of precipitation are highly lacking. Therefore, spatially distributed precipitation products developed at global/regional scale are often used in several scientific disciplines. However, large uncertainties in precipitation estimates of such precipitation data sets often lead to suboptimal outcomes. In this study, performance of 27 widely used gridded precipitation products belonging to three different categories of gauge‐based, reanalysis and merged products is evaluated with respect to high‐quality reference climatologies of mean monthly precipitation. Widely used statistical measures and quantitative analysis techniques are used to analyse the spatial patterns and quantitative distribution of mean monthly, seasonal and annual precipitation at sub‐regional scale. Mean annual precipitation estimates of the gridded data sets are cross validated with the corresponding adjusted streamflows using Turc‐Budyko non‐dimensional analysis. Results reveal poor to moderately good performance of the gridded data sets. Marked differences in spatiotemporal and quantitative distribution of precipitation are found among the data sets. All data sets are consistent in their patterns showing negative or dry bias in wet areas and positive or wet bias in dry areas, although considerable differences in the magnitudes of the biases are noticed at sub‐regional scale. None of the data sets is equally good for all sub‐regions due to very high spatiotemporal variability in their performance at sub‐regional scale. Gauge‐based and merged products performed better in dry regions and during monsoon season, while reanalysis products provided better estimates in wet areas and during winter months. GPCC V8, ERA5 and MSWEP2.2 are found better than their counter‐grouped data sets. Overall, ERA5 is found most acceptable for all sub‐regions, particularly at higher‐altitudes, in wet areas and during winter months.

Correlation of MSH2 exonic deletions and protein downregulation with breast cancer biomarkers and outcome in Pakistani women/patients - Saima Shakil Malik; Sumaira Mubarik; Ayesha Aftab; Ranjha Khan; Nosheen Masood; Muhammad Asif; Razia Bano (Environmental Science and Pollution Research, 2021)

Anti-urease and cytotoxic activity of 1-Nitro-2-phenylethane and Nerolidol; two major compounds isolated from the seeds of Dennettia tripetala - Samuel E. Ugheighele; Kate E. Imafidon; Muhammad I. Choudhary; Ahmed Shakil; Majid Khan; Zaid A. Sherwani; Zaheer Ul-Haq (Medicinal Chemistry Research, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

An insight into clinical outcome of XPG polymorphisms in breast cancer - Saima Shakil Malik; Sumaira Mubarik; Nosheen Masood; Muhammad Tahir Khadim (Molecular Biology Reports, 2018)

Ensembling Downscaling Techniques and Multiple GCMs to Improve Climate Change Predictions in Cryosphere Scarcely-Gauged Catchment - Muhammad Azmat; Muhammad Uzair Qamar; Shakil Ahmed; Muhammad Adnan Shahid; Ejaz Hussain; Sajjad Ahmad; Rao Arsalan Khushnood (Water Resources Management, 2018)

Synthesis, computational studies and biological evaluation of new 1-acetyl-3-aryl thiourea derivatives as potent cholinesterase inhibitors - Aamer Saeed; Muhammad Shakil Shah; Fayaz Ali Larik; Shafi Ullah Khan; Pervaiz Ali Channar; Ulrich Flörke; Jamshed Iqbal (Medicinal Chemistry Research, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)